2018
DOI: 10.1590/1678-4162-9675
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética de 12 loci de microssatélites em galinhas crioulas Canela-Preta

Abstract: RESUMO Esta pesquisa foi realizada com o objetivo de se conhecer a variabilidade genética de 12 loci de microssatélites em galinhas crioulas Canela-Preta. Foram coletadas amostras de sangue de 118 galinhas crioulas Canela-Preta, provenientes de três municípios do estado do Piauí (Oeiras, Queimada Nova e Teresina). Após extração do DNA, foram utilizados marcadores para 12 loci de microssatélites: LEI0192, LEI0209, LEI0212, LEI0217, LEI0221, LEI0234, LEI0237, LEI0248, LEI0258, MCW0081, MCW0183 e MCW0213, que for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The comparisons between females and males with the same plumage color reared in different breeding systems showed that Canela-Preta chickens have an excellent response to the characteristics of free-range production (e.g., slaughter age above 85 days, greater grazing activity, movement, intake of forage, insects, and earthworms). Such characteristics corroborate the native condition of Canela-Preta chickens, that is, the adaptation to the edaphoclimatic conditions of northeastern Brazil (Dias et al, 2016;Carvalho et al, 2017). Therefore, if producers provide good welfare conditions for those birds, with proper feeding management, birds will respond well to the semiconfinement system (Santos, 2005).…”
Section: The Growth Pattern Of Brazilian Canela-preta Chickens With D...supporting
confidence: 56%
See 2 more Smart Citations
“…The comparisons between females and males with the same plumage color reared in different breeding systems showed that Canela-Preta chickens have an excellent response to the characteristics of free-range production (e.g., slaughter age above 85 days, greater grazing activity, movement, intake of forage, insects, and earthworms). Such characteristics corroborate the native condition of Canela-Preta chickens, that is, the adaptation to the edaphoclimatic conditions of northeastern Brazil (Dias et al, 2016;Carvalho et al, 2017). Therefore, if producers provide good welfare conditions for those birds, with proper feeding management, birds will respond well to the semiconfinement system (Santos, 2005).…”
Section: The Growth Pattern Of Brazilian Canela-preta Chickens With D...supporting
confidence: 56%
“…The differences observed between the growth curves of males and females can be due to the sexual dimorphism in the Canela-Preta breed (Carvalho et al, 2017). This phenomenon resulted in different adult body weights and growth rates for males and females (Figure 2).…”
Section: The Growth Pattern Of Brazilian Canela-preta Chickens With D...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, microsatellite markers have been widely used to describe the genetic diversity and structure of populations of different domestic species. In general, comparative studies on the genetic diversity and relationship of different breeds consolidate a wide database that can be used for conservation, selection schemes, and understanding of the evolution of species [ 8 ].…”
Section: Introductionmentioning
confidence: 99%